Performance of biomass and exopolysaccharide production from the medicinal mushroom Ganoderma lucidum in a new fabricated Air-L-Shaped Bioreactor (ALSB) - Supramani, Sugenendran; Rejab, Nur Ardiyana; Ilham, Zul; Ahmad, Rahayu; Show, Pau-Loke; Ibrahim, Mohamad Faizal; Wan Mohtar, Wan Abd Al Qadr Imad (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Conventional stirred-tank bioreactor (STR) designs are optimised for cultures of bacteria but not fungal cultures; therefore, a new Air-L-Shaped Bioreactor (ALSB) was fabricated. The ALSB was designed to eliminate the wall growth and clumping of fungal mycelium in STRs. Ganoderma lucidum was used as a fungal model and its biomass and exopolysaccharide (EPS) production were maximised by optimising the agitation rate, glucose concentration, initial pH, and aeration via response surface methodology (RSM). The ALSB system generated 7.8 g/L of biomass (biomass optimised conditions: 110 rpm, 24 g/L glucose, pH 5.6, and 3 v/v of aeration) and 4.4 g/L of EPS (EPS optimised conditions: 90 rpm, 30 g/L glucose, pH 4, and 2.5 v/v of aeration). In combination, for both optimised conditions, biomass (7.9 g/L) and EPS (4.6 g/L) were produced at 110 rpm, 30 g/L glucose, pH 4, and 3 v/v of aeration with minimal wall growth. The data prove that the ALSB is a blueprint for efficient economical fungal cultivation.